PEMBELAJARAN KONTROL SISTEM PNEUMATIK SEBAGAI PENUNJANG KOMPETENSI SISTEM HIDROLIK DAN PNEUMATIK DI SMK NEGERI 1 ADIWERNA - Nur Aidi Ariyanto; M. Taufik Qurohman; Andre Budhi Hendrawan (Jurnal Pengabdian Masyarakat Teknik, 2022)
Community Service Activities carried out are providing understanding and thinking patterns about pneumatic systems control that work electro-pneumatically to students of SMK Negeri 1 Adiwerna grade XII majoring in Technical Light Vehicle (TLV). Knowledge of pneumatic systems is one of the competencies that are usually difficult to understand by TLV students. Whereas pneumatic systems have many applications in the industrial world. By using a facility in the form of an Electro-Pneumatic Trainer, the delivery of discussions about pneumatic system control will be more easily understood by students. By referring to the wiring diagram, students are explained to be able to read and understand the intent and working process of the pneumatic systems control and put it into practice immediately. There are 3 types of pneumatic systems control delivered, (1) single-cylinder pneumatic control systems, (2) single-cycle multiple cylinder pneumatic control systems, (3) continuous cycle multiple cylinder pneumatic control systems. Students are very enthusiastic about receiving explanations and practicing all three control systems.